2009
DOI: 10.1111/j.1365-2133.2009.09228.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatological surgery: a comparison of activity and outcomes in primary and secondary care

Abstract: This study presents a strong case for dermatologists to continue to provide the lead in diagnosis of skin lesions, and in selection and execution of dermatological surgical procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…(18)reportingsignificantdifferences between complete excision rates in nonmelanoma skin cancer between dermatologists versus plastic surgeons and GPs.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…(18)reportingsignificantdifferences between complete excision rates in nonmelanoma skin cancer between dermatologists versus plastic surgeons and GPs.…”
Section: Discussionmentioning
confidence: 97%
“…Intensive training on recognition and treatment of skin malignancies is therefore indispensable. The dermatologist must continue to have a leading role in diagnosis and (surgical) treatment of non-melanoma skin cancer, as advised by Goulding et al (18).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies found similar proportions of complete BCC excisions; however, these studies lack a sample size calculation, subgroup analyses per tumor site and histological subtype, and logistic regressions [8][9][10][11]. Dermatologists probably excise BCC more often complete than GPs and plastic surgeons because dermatologists are specifically trained in BCC care during their 5 years of specialization, and dermatologists are more experienced in BCC care due to the high case load in their daily practice.…”
Section: Discussionmentioning
confidence: 97%
“…4 Surgery is still considered the first-line treatment in different European countries, and 57-87% of all BCCs are still treated by standard excision (SE). [5][6][7][8] In the current observational literature, 5-year recurrence rates for Mohs micrographic surgery (MMS) are reported to be 1Á0-6Á5% for primary BCC and 4Á0-10Á0% for recurrent tumours. 9-15 A large, 10-year followup randomized controlled trial of high-risk facial BCCs showed a difference of 7Á8% for primary and 9Á6% for recurrent BCCs in favour of MMS over SE, although only the latter reached statistical significance.…”
Section: Discussionmentioning
confidence: 99%